L’apprentissage autorégulé : quand la métacognition orchestre motivation, volition et cognition - Mireille Houart (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In our work on volition (starting work and staying the course in the first year of higher education), different concepts related to self-regulated learning have been addressed : metacognition, motivation, cognition and volition. These approaches have led us to develop a model of self-regulated learning that integrates the different facets of learning : motivation, volition, cognition and metacognition. This model aims to help teachers and trainers guide students in their autonomous learning. Indeed, this model should allow the education stakeholders to mobilize the knowledge acquired about these different concepts, to identify in which part of the learning process the students’ difficulties lie and then to support them in a targeted way towards more autonomous learning.Including metacognition in a model of self-regulated learning preserves the essential components of metacognition in order to design pedagogical actions : metacognitive strategies, metacognitive knowledge and metacognitive experiences.Integrating volition into our model offers the advantage of allowing teachers to take account of a difficulty encountered by a majority of students at present (starting work and remaining focused), and therefore helping them to act pedagogically.Our objective here is to describe this model in theory and in practice. And so, after a description of its principles, we will present an example based on a real situation asking for autonomous learning. This will enable us to establish links with the model, and to suggest concrete pedagogical actions.Finally, since volition is problematic for 75 % of students we propose and describe how to operate and conduct two group activities with students. These group activities aim to help students to start work and to maintain their effort until they achieve their goal.